Deep-water flow in the Faroe Bank Channel 1983 - Deep-water fow in the Faroe Bank Channel 1983 - Borenäs, Karin (SMHI - Swedish Meteorological and Hydrological Institute, 2019)
Measurements in the Faroe Bank Channel from the research vessel N/O SVANIC in May 1983.

Mätningar av vattenströmmar i Färöbankens kanal (Faroe Bank Channel) från forskningsfartyget N/O SVANIC i maj 1983.
Vattenströmmar i Färöbankens kanal 1983
Current measurements in the Faroe Bank Channel
Keywords: OCEAN CURRENTS; ocean current; Hydrography; Hydrografi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav